The Role of Decadal Kelvin Wave in the Western of Sumatra and Along the South Coast of Java using Frequency-Wavenumber 2D Spectral Analysis - Hanah Khoirunnisa; Reno Arif Rachman; Nining Sari Ningsih; Fadli Syamsudin (UIR PRESS, 2020)
This study observed the decadal variability of the sea surface height anomaly (SSHA) and identified the decadal Kelvin wave propagation along west-Sumatra and south coast of Java. SSHA data and the vertical distribution of sea temperature for 64 years from HYCOM model resulted has already used in this research. There are several methods to identify the propagation of decadal Kelvin wave. These methods were low-pass filter by cut-off 1 and 8 years, visual analytic by using Hovmӧller diagram method, and frequency-wavenumber 2D spectral analysis to identify the Kelvin wave propagation and its period. The decadal Kelvin wave could be observed in west coast of Sumatra and along south coast of Java. There are three propagations of decadal Kelvin wave and their velocities were 1.029x10-3 m/s (1974 – 1976), 0.21 m/s (1985 – 1986), and 6.86x10-4 m/s for 1998 to 2001 trough west Sumatra and southern Java. The frequency-wavenumber 2D spectral analysis produced the improvement of Kelvin wave and it has the period of 7.25 years. The occurrence of the Kelvin wave has a relation to IOD index. The average of the IOD index when the decadal Kelvin wave was occurring must be the negative value, its value was a -0.21.